Postpartum multi-vessel spontaneous coronary artery dissection in the setting of cocaine and amphetamine use: a case report. Issue 1 (22nd December 2020) - McGovern, Laurna; Coughlan, J J; Murphy, Ross; Edroos, Sadat
Abstract: Background : Spontaneous coronary artery dissection (SCAD) is a recognized cause of acute coronary syndrome (ACS). Pregnancy, the postpartum period, and illicit drug use have all been reported as potential triggers. Case summary : We describe the case of a 41-year-old patient who presented to the emergency department with chest pain in the setting of recent cocaine and amphetamine use. The patient was 4 months postpartum following an uncomplicated pregnancy. Past medical history was non-contributory, with no known risk factors for ischaemic heart disease. Electrocardiogram was normal but high-sensitivity troponin T was significantly elevated. Coronary angiography revealed multi-vessel SCAD. This was managed conservatively as the patient remained clinically stable and pain free without high-risk anatomy (left main stem or proximal two-vessel coronary artery dissection). Discussion : Spontaneous coronary artery dissection must be considered in a postpartum patient presenting with ACS, particularly in the context of environmental stressors such as illicit drug use. Coronary angiography is key to determine diagnosis and guide management. Conservative therapy is favoured, except for patients with ongoing ischaemia, haemodynamic instability, and left main stem involvement. In this case, we suspect SCAD occurred due to the haemodynamic effects of cocaine and amphetamines in the context of structural arterial changes of the postpartum state.